4(9-3b)=-72

Simple and best practice solution for 4(9-3b)=-72 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(9-3b)=-72 equation:


b in (-oo:+oo)

4*(9-(3*b)) = -72 // + 72

4*(9-(3*b))+72 = 0

4*(9-3*b)+72 = 0

4*(9-3*b)+72 = 0

108-12*b = 0

108-12*b = 0

108-12*b = 0 // - 108

-12*b = -108 // : -12

b = -108/(-12)

b = 9

b = 9

See similar equations:

| 3(-3-3a)=-108 | | 5(-7m+2)=-25 | | 5(9-4t)=-155 | | 7(-7+2t)=-217 | | 4(-3n+8)=104 | | 6(-1k-7)=30 | | 7(-9-4x)=133 | | (3x-4)(7x+1)= | | 3(6w+9)=-153 | | 4(6+7x)=-200 | | 7(9-2a)=-7 | | 6(2a-8)=-36 | | 5(5+3t)=130 | | 5(-1k+3)=5 | | (n-3)(n-7)= | | 2(-3+n)=-6 | | 4(3k-4)=104 | | 3(-10+4n)=-114 | | 4i/3+3i | | 3(-10-4t)=6 | | 2(-4+k)=16 | | 5(-5a-10)=-300 | | 5(-1m+8)=-15 | | 2(-8+7n)=-184 | | 6(1w+10)=132 | | 4(5+m)=64 | | 5(-1m+7)=-10 | | 4(-8-6n)=184 | | 4(6k+4)=256 | | x+9/5=11/5 | | 7(6-7d)=42 | | 4(-2d-3)=76 |

Equations solver categories